2020
DOI: 10.1002/nbm.4319
|View full text |Cite
|
Sign up to set email alerts
|

Robust arterial transit time and cerebral blood flow estimation using combined acquisition of Hadamard‐encoded multi‐delay and long‐labeled long‐delay pseudo‐continuous arterial spin labeling: a simulation and in vivo study

Abstract: Arterial transit time (ATT) prolongation causes an error of cerebral blood flow (CBF) measurement during arterial spin labeling (ASL). To improve the accuracy of ATT and CBF in patients with prolonged ATT, we propose a robust ATT and CBF estimation method for clinical practice. The proposed method consists of a three‐delay Hadamard‐encoded pseudo‐continuous ASL (H‐pCASL) with an additional‐encoding and single‐delay with long‐labeled long‐delay (1dLLLD) acquisition. The additional‐encoding allows for the recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…The advantage of the combination of the multidelay and LLLD scans was previously reported by Ishida et al in a study that compared seven-delay scan and three-delay scans combined with LLSD and LLLD, in which they examined one patient with moyamoya disease in addition to simulation and healthy volunteer studies. 35 In their study, data combination was performed on a perfusion image basis, in which CBF was computed as the least-squares solution of the linear problem B ¼ Af , where A is a column vector of the coefficients of each bolus from Eq. 1 and B is a column vector of the measured perfusion difference signal of each bolus.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the combination of the multidelay and LLLD scans was previously reported by Ishida et al in a study that compared seven-delay scan and three-delay scans combined with LLSD and LLLD, in which they examined one patient with moyamoya disease in addition to simulation and healthy volunteer studies. 35 In their study, data combination was performed on a perfusion image basis, in which CBF was computed as the least-squares solution of the linear problem B ¼ Af , where A is a column vector of the coefficients of each bolus from Eq. 1 and B is a column vector of the measured perfusion difference signal of each bolus.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we adopted the narrow margins and data-driven initial value estimation that had already established robustness in clinical cases. 29,[39][40][41] ATT, TTT, and CBF were estimated by collating the observed signals with a lookup table on voxel-by-voxels (Equation 8). (6.1)…”
Section: Experiments 2: Data Processing For Multiparameter Estimationmentioning
confidence: 99%
“…Second, the initial CBF values were calculated by a least-squares solution using the dataset with DANTE. 39 Based on these initial values, lookup tables were computed on a voxel-by-voxel basis by calculating the ground truth signals using Equations ( 5) and (6) with the following conditions: 9 ATTs (initial ATT ± 200 ms with 50 ms interval), 21 TTTs (initial TTT ± 500 ms with 50 ms interval), 41 CBFs (initial CBF ± 20 mL/100 g/min with 1.0 mL/100 g/min interval). Each voxel has a different lookup table that is generated for 7749 hemodynamic conditions based on the initial values and predefined margins.…”
Section: Experiments 2: Data Processing For Multiparameter Estimationmentioning
confidence: 99%
“…3 More recently, Ishida et al proposed a combination strategy of Hadamard-type multidelay ASL (delay encode = 3) and LLLD ASL, and demonstrated its advantages and the clinical feasibility of CBF estimation in areas of prolonged ATT. 4 In this issue of JMRI, the article entitled "Arterial Transit Time-Based Multidelay Combination Strategy Improves Arterial Spin Labeling Cerebral Blood Flow Measurement Accuracy in Severe Steno-Occlusive Diseases" proposes a new combination strategy of multidelay ASL and LLLD ASL to overcome issues associated with the complicated hemodynamics observed in severe steno-occlusive diseases. 5 First, the authors conducted multidelay ASL using a Hadamard-type pulse sequence as well as LLLD ASL by additional scanning.…”
mentioning
confidence: 99%
“…Fan et al examined 15 Moyamoya patients with standard ASL, multidelay ASL, and LLLD ASL, and showed that LLLD ASL demonstrated stronger CBF correlations with positron emission tomography (PET) scans than multidelay ASL, especially in cases of long transit delay 3 . More recently, Ishida et al proposed a combination strategy of Hadamard‐type multidelay ASL (delay encode = 3) and LLLD ASL, and demonstrated its advantages and the clinical feasibility of CBF estimation in areas of prolonged ATT 4 …”
mentioning
confidence: 99%